PENDIDIKAN ISLAM DALAM PRESPEKTIF SYED M.NUQIB AL-ATTAS - Shodikin Shodikin; Ikfi Khoulita; Hani Adi Wijono (ISLAMIDA Journal of Islamic Studies, 2024)
Instinctively, humans always try to base their desires for life on something that is considered to have absolute power. This can be seen in the history of human life, from classical times to contemporary conditions. The condition of the human soul which views that worldly life is only a medium for achieving true life, then utilizes worldly facilities effectively and efficiently in achieving happiness in life both in this world and the hereafter. Based on the explanation above, the author took the title Islamic Education from the Perspective of Syed M.Nuqib Al-Attas. Islamic Education from the Perspective of Syed M.Nuqib Al-Attas - The aim of Islamic education according to al-Attas' perspective is not only to train the mind, but also to train the entire potential of a human being. Islamic Education in the Perspective of Syed M.Nuqib Al-Attas - Functionally Islamic education is an effort by Muslim humans to form al-insan al-kamil. Al-Attas's opinion is that the structure of knowledge and the Islamic education curriculum should describe humans and their nature, which must be implemented first at the university level. The division of reason is theoretical reason (al 'aql al-nazhari), and practical reason (al-aql al-'amali).